Critical appraisal of belinostat in the management of T-cell lymphoma – patient considerations - Bodiford A (Dove Medical Press, 2015)
Andrew Bodiford,1 Mahsa S Talbott,1 Nishitha M Reddy,2 1Department of Pharmacy, 2Division of Hematology and Oncology, Department of Medicine, Vanderbilt University Medical Center, Nashville, TN, USA Abstract: The histone deacetylase inhibitor (HDACi), belinostat, is an emerging and novel therapeutic option for patients diagnosed with relapsed/refractory peripheral T-cell lymphoma (PTCL). The PTCLs are comprised of multiple subtypes that occur in less than one per 100,000 cases in the USA. The incidence of these malignancies is rare, thus limited evidence is available. The most appropriate treatment modality has not been established. The most current recommended option is combination chemotherapy or enrollment in a clinical trial. T-cell lymphomas have emerged as a disease with marked epigenetic dysregulation. HDACi are an innovative and emerging medication class gaining increased attention in the treatment of T-cell lymphomas. There is a need to evaluate their potential place in the treatment of patients diagnosed with PTCL. Currently, the largest study evaluating belinostat use in this patient population is the BELIEF study. The BELIEF study is a single-arm, Phase II clinical trial, evaluating the use of belinostat in patients with refractory or relapsed PTCL. The primary outcome, objective response rate, was 26%, with 11% achieving a complete response and 15% a partial response. This study presents a potential novel therapeutic option in the treatment of these patients. In this paper, we review therapeutic options for PTCL and present the recent data on the role of HDACi, specifically belinostat, in the treatment of patients with relapsed/refractory PTCL. Keywords: peripheral T-cell lymphoma, novel agents, histone deacetylase inhibitor